2019
DOI: 10.1007/s42452-019-0588-z
|View full text |Cite
|
Sign up to set email alerts
|

Sub-bottom acoustic profiling as a remediation assessment tool for contaminated lakes

Abstract: Frame Lake, a small (88.4 ha), shallow (< 6.5 m maximum depth), high-latitude lake found within the city limits of Yellowknife, Northwest Territories, Canada was selected due to the known legacy contamination of the lake's sediments to test the feasibility of using seismic sub-bottom profiling to estimate total volumes of heavy metal contaminated sediments in lacustrine environments. To ground-truth the sub-bottom profiling results, physical and ICP-MS analyses were carried out on freeze cores collected from F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Spatial and nonspatial statistical methods, such as kriging, have played an important role in geochemical pattern recognition in lakes [49]. Results displayed in a spatial manner facilitate the identification of depositional areas and catchment influences, which is important for designing subsequent sampling plans for future field work (e.g., [50]). Ordinary kriging, which is the most widely used form of spatial interpolation among the various kriging methodologies [51], was used to generate continuous maps of the results throughout the entirety of the Harvey Lake basin.…”
Section: Geospatial Data Handlingmentioning
confidence: 99%
“…Spatial and nonspatial statistical methods, such as kriging, have played an important role in geochemical pattern recognition in lakes [49]. Results displayed in a spatial manner facilitate the identification of depositional areas and catchment influences, which is important for designing subsequent sampling plans for future field work (e.g., [50]). Ordinary kriging, which is the most widely used form of spatial interpolation among the various kriging methodologies [51], was used to generate continuous maps of the results throughout the entirety of the Harvey Lake basin.…”
Section: Geospatial Data Handlingmentioning
confidence: 99%
“…Of the controls on arcellinidan distribution identified in Frame Lake, Ca (9.5%; pvalue < 0.004), Olsen P (10.5%; p-value < 0.005), and especially As (15.8%; pvalue < 0.003) contributed the most toward explaining the variance in the arcellinidan distribution. The observation that As is the most significant control in Frame Lake is not surprising given the results of previous studies that have identified the impact of As contamination on the lake's ecology and sediment quality (Drizawsky andWilson, 2013, 2016;Menard et al, 2019).…”
Section: Frame Lakementioning
confidence: 92%
“…Frame Lake has a relatively small surface area (88.4 ha) with a maximum length and width of 1.75 km and ~ 1 km, respectively (Healey, 1973;Dirszowsky and Wilson, 2016). The lake has a maximum depth of 4.5m in the southern basin and 5.5m in the northern basin (Menard et al, 2019). In terms of morphology, Frame Lake is of an elongate shape (southwest-northeast trend) that widens toward the northeastern end of the lake (Figure 3.1B).…”
Section: Frame Lakementioning
confidence: 99%
See 2 more Smart Citations